Nitrogen starvation leads to TOR kinase-mediated downregulation of fatty acid synthesis in the algae Chlorella sorokiniana and Chlamydomonas reinhardtii - Vijayan, Jithesh; Alvarez, Sophie; Naldrett, Michael J.; Morse, Wyatt; Maliva, Amanda; Wase, Nishikant; Riekhof, Wayne R. (BMC plant biology, 2024)
When subject to stress conditions such as nutrient limitation microalgae accumulate triacylglycerol (TAG). Fatty acid, a substrate for TAG synthesis is derived from de novo synthesis or by membrane remodeling. The model industrial alga Chlorellasorokiniana accumulates TAG and other storage compounds under nitrogen (N)-limited growth. Molecular mechanisms underlying these processes are still to be elucidated. Previously we used transcriptomics to explore the regulation of TAG synthesis in C. sorokiniana. Surprisingly, our analysis showed that the expression of several key genes encoding enzymes involved in plastidic fatty acid synthesis are significantly repressed. Metabolic labeling with radiolabeled acetate showed that de novo fatty acid synthesis is indeed downregulated under N-limitation. Likewise, inhibition of the Target of Rapamycin kinase (TOR), a key regulator of metabolism and growth, decreased fatty acid synthesis. We compared the changes in proteins and phosphoprotein abundance using a proteomics and phosphoproteomics approach in C. sorokiniana cells under N-limitation or TOR inhibition and found extensive overlap between the N-limited and TOR-inhibited conditions. We also identified changes in the phosphorylation status of TOR complex proteins, TOR-kinase, and RAPTOR, under N-limitation. This indicates that TOR signaling is altered in a nitrogen-dependent manner. We find that TOR-mediated metabolic remodeling of fatty acid synthesis under N-limitation is conserved in the chlorophyte algae Chlorella sorokiniana and Chlamydomonas reinhardtii. Our results indicate that under N-limitation there is significant metabolic remodeling, including fatty acid synthesis, mediated by TOR signaling. This process is conserved across chlorophyte algae. Using proteomic and phosphoproteomic analysis, we show that N-limitation affects TOR signaling and this in-turn affects the metabolic status of the cells. This study presents a link between N-limitation, TOR signaling and fatty acid synthesis in green-lineage.